PENGARUH DISIPLIN KERJA, MOTIVASI DAN PRESTASI KERJA TERHADA KINERJA KARYAWAN BERDASARKAN PRESEPSI KARYAWAN PT. INDOMARCO PRISMATAMA WILAYAH INDOMARET BALIKPAPAN TIMUR - Nainggolan, Hermin; Susilo , Erwin; Mutiara , Beatrix (Jurnal Manajemen dan Bisnis, 2025)
This study aims to determine the influence of work discipline, work motivation and work performance on the performance of employees of PT. Indomarco Prismatama Indomaret East Balikpapan Region partially and simultaneously. The research data was obtained from employee performance reports for 5 years from the period 2020 - 2024 with a total of 99 employees (saturated sample) by using multiple linear regression analysis test tools. Based on the results of the hypothesis research test, it was partially shown that the independent variable (work discipline X1) partially had a negative and significant effect on (performance) in obtaining a calculated value of (-4.461) < ttable (1.661) and significance (0.001) < 0.05. The independent variable (motivation X2) partially had a negative and significant effect on (performance) obtained a tcount value of (27.924) > ttable (1.661) and significance (0.001) < 0.05. The independent variable (work performance X3) partially had a positive and insignificant effect on (performance) obtained a calculated value of (1.244) > ttable (1.661) and significance (0.217) < 0.05. Simultaneously, the variables of work discipline, motivation, and work performance had a significant effect on the performance obtained a calculated value of 22,738,965 > from Fhitung = 2.700 and a significant value of 0.001 < 0.05.